2010
DOI: 10.1042/bj20100155
|View full text |Cite
|
Sign up to set email alerts
|

The potency of the fs260 connexin43 mutant to impair keratinocyte differentiation is distinct from other disease-linked connexin43 mutants

Abstract: Although there are currently 62 mutants of Cx43 (connexin43) that can cause ODDD (oculodentodigital dysplasia), only two mutants have also been reported to cause palmar plantar hyperkeratosis. To determine how mutants of Cx43 can lead to this skin disease, REKs (rat epidermal keratinocytes) were engineered to express an ODDD-associated Cx43 mutant always linked to skin disease (fs260), an ODDD-linked Cx43 mutant which has been reported to sometimes cause skin disease (fs230), Cx43 mutants which cause ODDD only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…There appeared to be a notable reduction in gap junction plaques in mutant mice, and by definition a predicted reduction in gap junctional intercellular communication, but this is somewhat difficult to conclude with certainty as a putative upregulation of Cx43 could mask the punctate gap junction plaque profile. We previously observed significantly reduced gap junctional coupling when the G60S mutant was expressed in reference cell lines that contained or lacked endogenous Cx43 (McLachlan et al, 2005;Churko et al, 2010) as well as in primary cardiomyocytes (Manias et al, 2008) or osteoblasts (McLachlan et al, 2008) obtained from G60S mutant mice. Thus, it is highly likely that resident cell types of the hair follicle also have reduced gap junctional coupling, which could in turn impact the growth and development of the hair follicle and the hair fiber.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…There appeared to be a notable reduction in gap junction plaques in mutant mice, and by definition a predicted reduction in gap junctional intercellular communication, but this is somewhat difficult to conclude with certainty as a putative upregulation of Cx43 could mask the punctate gap junction plaque profile. We previously observed significantly reduced gap junctional coupling when the G60S mutant was expressed in reference cell lines that contained or lacked endogenous Cx43 (McLachlan et al, 2005;Churko et al, 2010) as well as in primary cardiomyocytes (Manias et al, 2008) or osteoblasts (McLachlan et al, 2008) obtained from G60S mutant mice. Thus, it is highly likely that resident cell types of the hair follicle also have reduced gap junctional coupling, which could in turn impact the growth and development of the hair follicle and the hair fiber.…”
Section: Discussionmentioning
confidence: 95%
“…However, hair from two patients (parent and sibling) expressing the G143S mutant revealed cuticle weathering. demonstrated that keratinocytes expressing the frameshift 260 mutant were more potent than several missense Cx43 mutants at altering cell coupling levels, epidermal organotypic formation, and transepithelial resistance (Churko et al, 2010). Alternatively, patient disease heterogeneity may extend beyond these criteria as phenotype variability is also seen in mutant mice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Originally, ODDD was thought to be exclusively a disease linked to autosomal dominant mutations which would allow for the possibility that the allele harboring the wild-type gene could suffice to provide sufficient Cx43-based GJIC and allow patients to maintain essential organ function as seems to be the case in the heart where Cx43 is abundant (Gros and Jongsma, 1996). Many of these autosomal dominant mutants have been categorized by us and others as loss-of-function mutants, gain-of-hemichannel function mutants or dominant-negative mutants on co-expressed wild-type Cx43 (Churko et al, 2011a;Churko et al, 2012;Churko et al, 2010;Churko et al, 2011b;Dobrowolski et al, 2009;Dobrowolski et al, 2008;Dobrowolski et al, 2007;Flenniken et al, 2005;Gong et al, 2007;Gong et al, 2006;Lai et al, 2006;Langlois et al, 2007;Lorentz et al, 2012;Manias et al, 2008;McLachlan et al, 2005;McLachlan et al, 2008;Musa et al, 2009;Shao et al, 2012;Shibayama et al, 2005;Stewart et al, 2013;Toth et al, 2010). However, our understanding of the characteristics of Cx43 mutants became more complicated when two autosomal recessive mutations were identified that encoded a severely truncated Cx43 (R33X) (Richardson et al, 2006) and an arginine to a histidine (R76H) substitution within the domain predicted to be at the extreme region of the 1st extracellular loop (Pizzuti et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We used HeLa cells for coimmunoprecipitation, because of the low transfection efficiencies of BxPC3 and Capan-1 cells. The results showed that Cells expressing YA/VD-Cx43 assemble gap junctions Various Cx subtypes have been shown to oligomerize to form heteromeric connexons that are incorporated into gap-junctional plaques (Jiang and Goodenough, 1996;Valiunas et al, 2001;Churko et al, 2010). We hypothesized that the sorting-motif mutant YA/VD-Cx43, by forming heteromers with the endogenous Cx43, might affect junction assembly by inhibiting endocytosis.…”
Section: Endocytosis Of Cx43mentioning
confidence: 99%